Long-term survival without recurrence after surgery for gastric yolk sac tumor-like carcinoma: a case report - Umeda, Hibiki (Surg Case Rep, 2021)
BACKGROUND: Gastric yolk sac tumor (YST)-like carcinoma is extremely rare, and its prognosis is poor, because most patients have widespread metastases at the time of diagnosis. We report a case of gastric YST-like carcinoma with an adenocarcinoma component without metastases in which curative resection was performed. CASE PRESENTATION: A 77-year-old man complaining of melena and dizziness due to anemia was diagnosed with poorly differentiated adenocarcinoma in the gastric cardia, with a benign ulcer in the gastric body. He underwent total gastrectomy with D2 lymph node dissection for the tumor. Histological examination of the resected specimens revealed a mixture of reticular and glandular neoplastic components morphologically. In the reticular area, an endodermal sinus pattern and some Schiller–Duval bodies were confirmed. Gastric YST-like carcinoma with adenocarcinoma components, T2N0M0 Stage IB, was diagnosed. Immunohistochemical analysis showed that the YST was positive for carcinoembryonic antigen (CEA), alpha-fetoprotein (AFP) and p53. In contrast, the adenocarcinoma was positive for p53 and negative for CEA and AFP. The patient remained healthy as of 7 years postoperatively, with no recurrence. CONCLUSIONS: Routine medical examinations or endoscopic examinations for accidental symptom may be helpful for early diagnosis and good prognosis for gastric YST-like carcinoma, although the prognosis is generally poor.